TINJAUAN TERHADAP SISTEM MULTI PARTAI DALAM SISTEM PEMERINTAHAN PRESIDENSIAL DI INDONESIA PADA ERA REFORMASI - Zuhdi Arman; Dodi Haryono; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Amendment Act of 1945 that occurred in the era of reform based on a commitment to reinforce the Presidential system. In contrast, multi-party system in combination with the current presidential system of government is to encourage parties to form a coalition that actually weakens the presidential system itself. The Coalition is one of the institutions of parliamentary systems which negatively berekses governance. Practices in Indonesian coalition formed before the general election of President and Vice President dominated political dealings regarding the division of public office without the formulation of a common platform. In fact, the coalition was formed not ensure that parties who are members of the coalition that has a representative in the legislature will always support government programs. Therefore, this study aimed to understand the application of multi-party system in the Presidential system of government in Indonesia in the reform era at once formulate implications for the executive and legislative relations and the implementation of the ideal. This type of research can be can be classified into types of normative juridical research, because it makes the literature as the main focus. Source of data used, the primary legal materials, secondary law, and tertiary legal materials. Data collection techniques in this study using the method of literature study.The results showed that the application of multi-party system in the Presidential system of government actually weaken the presidential system and have implications for the executive and legislative relations. Three things that the implications are; First, the number of political parties' interests that conflict with government policy. Second, the absence of permanent coalition arrangement. Third, the weak position of President. Ideally the implementation of a multi-party system, in order to create stability in the Indonesian presidential system of government, then there are three (3) things that need to be addressed in our Presidential system, namely: First, the simplification of the political parties, the second, setting the coalition remains, and the third, the strengthening of institutional design presidency. The author suggests needed coalition of political parties that are permanently defined by the rules of Law clearer so that it will produce a strong and efficient government.Keywords: multi-party system, coalition, a Presidential system.